2008
DOI: 10.1270/jsbbs.58.367
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci controlling heading date among rice cultivars in the northernmost region of Japan

Abstract: Heading date is the major factor in the regional and seasonal adaptation of rice cultivars. Although many genes controlling heading date have been identified using several mapping populations, it is not clear which previously identified genes contribute to the variation of heading date in particular regions. However, great effort is needed to identify quantitative trait loci (QTLs) among rice cultivars in rice breeding programs in a particular region because they are genetically closely related. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 49 publications
0
23
0
1
Order By: Relevance
“…On the other hand, the heading date of Hitomebore in ODE09M was 2 days later than in C10S. In the case of Kirara 397, a cultivar with low photoperiodism (Fujino, 2003), the heading date in the control experiment in 2009 in Morioka (CO9M) was just 1 day later than that in C10S, despite the difference in summer temperature. The difference in heading date between the results from the ODE conditions designed to be an analog of Morioka (ODE09M-m) and those designed to be an analog of Sapporo (ODE09M-s) (indicated as in Fig.…”
Section: Feasibility Of Ode Experimentsmentioning
confidence: 91%
“…On the other hand, the heading date of Hitomebore in ODE09M was 2 days later than in C10S. In the case of Kirara 397, a cultivar with low photoperiodism (Fujino, 2003), the heading date in the control experiment in 2009 in Morioka (CO9M) was just 1 day later than that in C10S, despite the difference in summer temperature. The difference in heading date between the results from the ODE conditions designed to be an analog of Morioka (ODE09M-m) and those designed to be an analog of Sapporo (ODE09M-s) (indicated as in Fig.…”
Section: Feasibility Of Ode Experimentsmentioning
confidence: 91%
“…Whereas more than 90% of the obligate varieties are cultivated in tropical areas, most others in the temperate or subtropical areas are facultative, exhibiting a quantitative response to short clays and even flowering under continuous light (Yu and Yao, 1967). Those genotypes that either are cultivated in high-latitude temperate regions (Okumoto et al, 1996;Fujino, 2003) or which are early-season cultivars in low-latitude temperate areas are considered day-neutral (Shen et al, 1965).…”
Section: Factors Affecting Flowering Time In Ricementioning
confidence: 99%
“…Due to the importance of flowering time, much progress has been made in understanding its genetic control using natural variation in rice (Izawa 2007a, b;Yano et al 2001). In addition, genes controlling diverse phenotypic variations in flowering time, such as extremely early and late heading behavior, have been identified (Fujino and Sekiguchi 2005a, b;Fujino and Sekiguchi 2008;Nonoue et al 2008;Uga et al 2007). These studies have suggested that allelic variations contributing to the wide adaptability of rice may have occurred during the diversification of cultivated rice or may represent existing mutations in the gene pool prior to rice domestication.…”
Section: Introductionmentioning
confidence: 99%